Analisis Structure-Conduct-Performance Pasar Ternak Sapi Dan Kerbau untuk Meningkatkan Efisiensi Pemasaran - Firmansyah Firmansyah; Fahroerrozi Hoesni; Maruli Pahantus; Afriani H (Universitas Batanghari Jambi, 2021)
This study aims to analyze the market structure of cattle and buffalo in the livestock market based on the concentration of traders and buyers, barriers to market entry, market behavior and market performance of livestock, and their relationship to marketing efficiency. The sampling technique used is Stratified Random Sampling. Data analysis used Market Share analysis, Hirschman Herfindahl Index (IHH), CR4 (Concentration ratio for the biggest four), concentration ratio (Kr), market entry barriers with Minimum Efficient Scale (MES) analysis, and Price – Cost – Margin (PCM). The market structure of cattle and buffalo in the livestock market based on the concentration of traders is oligopsony with low concentration, based on the concentration of buyers it is an oligopsonistic market, and based on barriers to market entry it is categorized as high barriers to market entry. There is a relationship between market structure, market behavior and market performance on marketing efficiency in the livestock market.